Phytochemical Composition and Antioxidant Potential of Hyphaene thebaica Fruit - Muhammad Mubarak Dahiru; Margret Samuel Nadro (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The nature and application of medicinal plants in managing complications of various ailments are attributed partly to the presence of different phytochemicals. Oxidative stress due to increased levels of reactive oxygen species is a challenge in managing such conditions, which might lead to death. This study aimed to determine the phytochemical composition and antioxidant potential of Hyphaene thebaica fruit. The phytochemicals in methanol, aqueous, and ethyl acetate extract were qualitatively determined, followed by quantitation of the ethylacetate extract as it contains phytochemicals absent in the other extracts. The in vitro antioxidant potential of ethyl acetate extract of H. thebaica fruit was also determined. The result revealed the presence of alkaloids, saponins, terpenoids, and flavonoids in all the extracts. However, steroids were not detected in the aqueous extract, and glycoside was detected only in the ethylacetate extract. Flavonoids (5.80±0.20%) were higher than all the other phytochemicals in the ethyl acetate extract, followed by Saponins which were present up to 2.50±0.11%, then Terpenoids. Glycosides were present in higher amounts compared to Steroids. However, Alkaloids (0.08±0.05%) were in smaller quantities compared to the other phytochemicals quantified. The antioxidant activity showed a concentration-dependent increase in absorbance of the extract as displayed by the Standard (Ascorbic acid). The extract had an IC50 of 48.01%, significantly (p < 0.05) lower than that of the Standard (74.40%). Conclusively, H. thebaica can use as a medicinal plant due to its phytochemical composition and antioxidant activity.